Numerical and experimental investigation of thick composites manufacturing for wind turbines - Ammasai Sengodan, Ganapathi (2016)
The sizes of wind turbines and the blades have been increasing gradually in order to achieve high rated power at decreased cost. Use of composite materials for such blades depends on the effective manufacturing techniques, in both strength and cost sense. Although, the manufacturing guidelines and techniques from aerospace composites are being imitated for large wind turbine blades, they are not without challenges due to massive sizes of wind turbine components. Problems such as uneven resin flow, non-uniform thickness for a given number of plies, edge distortions and cure induced deformations still persist especially for thick composites. To this end, a virtual manufacturing procedure is a prerequisite to eliminate the “trial and error” method generally adopted to minimize these issues and improve the manufacturability of the composites. In the present thesis, a fully coupled finite element (FE) simulation procedure was developed to virtually manufacture the prepreg composites, to optimize the compaction and to control cure induced deformation of thick composite laminates. Vacuum bagging accessories have a significant influence on the parameters such as temperature, chemical kinetics and pressure distribution of the curing laminate. Therefore, initially, the characterization of materials used for vacuum bagging, such as the bleeder compaction and thermal conductivities of the bagging accessories were conducted to obtain the respective behavior. Consequently, the cure kinetic, rheological and thermo-mechanical behavior of a high temperature curing glass/epoxy prepreg were studied in order to develop an effective numerical simulation of composites manufacturing. Towards this, a two-dimensional thermo-chemical, resin flow and one-dimensional compaction of a thick carbon/epoxy prepreg fabrication assembly were modeled and simulated by using commercial FE software. The results obtained show the effect of bleeders and bagging accessories have on the temperature overshoot and the pressure distribution within the thick laminate and the bleeder. Different case studies revealed that the bleeder thickness and permeability significantly affect the amount of resin bleeding out from the curing laminate. This simulation procedure was extended to a three dimensional wind turbine blade spar cap manufacturing and the temperature and resin pressure distributions of the laminate and bleeder were obtained. Next, in order to predict the process induced deformations of the two dimensional laminate, a fully integrated numerical model is developed by accounting stress-deformation module in the already developed numerical simulation procedure. This module accounts the compaction and cure shrinkage (chemical & thermal) induced deformations of the laminate. A solution to minimize the distortion is discussed in detail. This procedure is extended to simulate a processing for curved laminate, where the shear moduli of the materials were observed to influence the final shape of the laminate. Subsequently, a pressure sensing device consisting of a fiber Bragg grating (FBG) was designed which is capable of measuring in-situ resin pressure with improved sensitivity even at low pressure. The main purpose of this sensor is to validate the developed numerical simulation procedure by measuring the resin pressure at selected location. In addition, it is used to monitor the resin pressure distribution of a curing laminate which is the key parameter that controls the strength, stiffness and nucleation of voids in the cured part. Finally, the application of the currently developed numerical procedure was demonstrated using two case studies. In the first, the process induced deformation of a scaled unidirectional wind turbine blade spar cap was presented. The edge curvature and the thickness variation along the length of the laminate were predicted and compared with the fabricated laminate. In the second, a method is proposed to manufacture composite laminates with variable cross section and mechanical properties without changing the number of layers involved or adding a ply-drop. In summary, the developed simulation procedure could be effectively used to virtually manufacture the thick unidirectional prepreg composites and control the process parameters concerning the goal of optimizing the process induced anomalies of the cured laminate.